Popper y la explicación cientifica1 - Carlos Verdugo Serna (Revista de Filosofia, 2005)
In his famous Logik der Forschung (1934) Popper indicates that a causal expla- nation of an event means to deduce a statement which describes it, using as premises of the deduction at least one natural law plus certain singular statements, the socalled initials conditions. According to this, I will claim that Popper should be considered as the founder and not simply an important precursor of the “deductivenomological” or “covering-law” model developed later by Hempel and Oppenheim in his classic article written in 1948 entitled “Studies in the Logic of Explanation”.